Supporting learning and teaching - Bold, Christine (London : Routledge, 2011)
'Supporting Teaching and Learning brings together theoretical perspectives, practical educational ideas and current academic debates to help students develop their understanding of core educational issues. With focus also on understanding the professional relationships necessary for quality learning, this updated second edition sets out to develop practitioners' study and reflective thinking skills. This book brings together chapters from well-qualified and positioned authors who cover a wide range of topics, themes and age ranges. Each chapter contains a statement of the author's values and beliefs and concludes with discussion starters, ideas for reflecting on practice and a list of useful resources. Topics covered in the book include: - The core subjects in the curriculum; - Information and Communications Technology, - Linguistic and cultural diversity; - Special educational needs; - Out-of-school learning; - Assessment; - Reflective practice and action research. Accessible, discursive and thought provoking, this book is essential reading for Foundation degree students, teaching assistants and those undertaking initial teacher training or Education Studies courses'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Reflective teaching; Action research in education